2000
DOI: 10.1128/jb.182.6.1499-1506.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Spore Peptidoglycan Hydrolase of Bacillus cereus : Biochemical Characterization and Nucleotide Sequence of the Corresponding Gene, sleL

Abstract: The exudate of germinated spores of B. cereus IFO 13597 in 0.15 M KCl-50 mM potassium phosphate (pH 7.0) contained a spore-lytic enzyme which has substrate specificity for fragmented spore cortex from wild-type organisms (cortical-fragment-lytic enzyme [CFLE]), in addition to a previously characterized germinationspecific hydrolase which acts on intact spore cortex (spore cortex-lytic enzyme [SCLE]) (R. Moriyama, S. Kudoh, S. Miyata, S. Nonobe, A. Hattori, and S. Makino, J. Bacteriol. 178:5330-5332, 1996). CFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 33 publications
9
63
0
Order By: Relevance
“…YaaH is 49 % identical to SleL of B. cereus, an enzyme demonstrated to have N-acetylglucosaminidase activity (Chen et al, 2000a). Although Chen et al (2000a) reported a germination defect, spore preparations of a yaaH mutant constructed by transfer of their null mutation into our standard laboratory strain (HR) background showed wild-type germination kinetics in -alanine, and outgrew normally (data not shown). The composition of dormant-spore peptidoglycan, as revealed by RP-HPLC analysis of muropeptides after Cellosyl digestion, was identical to wild-type traces published previously (Atrih et al, 1998).…”
Section: Testing Of Other Potential Lytic Enzymes For Their Role In Gmentioning
confidence: 99%
See 1 more Smart Citation
“…YaaH is 49 % identical to SleL of B. cereus, an enzyme demonstrated to have N-acetylglucosaminidase activity (Chen et al, 2000a). Although Chen et al (2000a) reported a germination defect, spore preparations of a yaaH mutant constructed by transfer of their null mutation into our standard laboratory strain (HR) background showed wild-type germination kinetics in -alanine, and outgrew normally (data not shown). The composition of dormant-spore peptidoglycan, as revealed by RP-HPLC analysis of muropeptides after Cellosyl digestion, was identical to wild-type traces published previously (Atrih et al, 1998).…”
Section: Testing Of Other Potential Lytic Enzymes For Their Role In Gmentioning
confidence: 99%
“…A ypeB mutant, defective in the gene downstream of sleB, shows the same germination defect as an sleB mutant (Boland et al, 2000). A cwlJ single mutant is blocked in late stages of germination, failing to phase-darken completely ; Chen et al (2000a) described a cortex-lytic enzyme of B. cereus (SleL) that is found in an active form in the germination exudate. It requires disrupted rather than intact spore peptidoglycan for its activity, and is therefore likely to act on a substrate that has already been cleaved by another lytic enzyme, such as SleB.…”
Section: Introductionmentioning
confidence: 99%
“…SleL is an N-acetylglucosaminidase that breaks b-1,4 glycosidic bonds found in cortical PG (Chen et al, 2000;Lambert & Popham, 2008). Previous studies show that sleL is expressed under the control of s E , which is active in the mother cell during early stages of sporulation (Chen et al, 2000;Kodama et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Germination has been studied in an array of Gram-positive spore-forming species including Clostridium perfringens (Chen et al, 1997;Miyata et al, 1995), Bacillus thuringiensis (Hu et al, 2007), Bacillus subtilis (Ishikawa et al, 1998;Kodama et al, 1999;Moriyama et al, 1996a), Bacillus megaterium (Foster & Johnstone, 1987;Setlow et al, 2009), Bacillus cereus (Chen et al, 2000;Makino et al, 1994;Moriyama et al, 1996b) and B. anthracis (Heffron et al, 2009(Heffron et al, , 2010Lambert & Popham, 2008;Liu et al, 2004). The B. anthracis germination cascade begins when nutrient germinants contact receptors within the spore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation